Application of Income Tax Calculation (PPH) Article 21 Permanent Employees at PT. Bumi Mitra Buton Abadi - Nenden Restu Hidayah; Karona Cahya Susena; Shendi Putra Alpino (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
This study aims to determine the tax payable report and withholding tax on permanent employees of PT. Bumi Buton Abadi Partners in accordance with the provisions of the Taxation Law No. 36 of 2008. The research method used is descriptive analysis method. The results of the study show that the deduction of income tax on permanent employees and tax returns is payable to PT. Bumi Mitra Buton Abadi has not been in accordance with the provisions of the Taxation Law No. 36 of 2008 due to a payment difference of Rp. 200,000.00. The payment difference is caused by differences in the use of the basis of Non-Taxable Income (PTKP). The PTKP basis used by PT. Bumi Mitra Buton Abadi still refers to the old regulations with a PTKP value of Rp. 48,000,000.00 while the calculation under the Taxation Law No. 36 of 2008 amounting to Rp. 72,000,000.00. With the payment difference, PT. Bumi Mitra Buton Abadi must make corrections in 2017.